INSIGHT INTO THE FOUR ASPECTS OF MAHASHAKTI ACCORDING TO THE WRITINGS OF SRI AUROBINDO - Deshmukh, Pooja; Fatnani, Kinjal; Bhatt, Pina (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Bharat i.e., India has a great history of having Saints, Revolutionaries, Yogi, Rishis of transmitting our traditional knowledge systems to the upcoming generations. Sri Aurobindo is one of the most eminent, renowned personalities in the history of India. The life and works of Sri Aurobindo are a living testimony to his victorious opening of the gates of a new horizon and by means of summarizing all his views from his writings, speeches, letters, we can get a bundle of eternal knowledge about creation of this world, the Supreme Shakti from the universe playing an inseparable role and many more.